2011
DOI: 10.1038/tpj.2011.32
|View full text |Cite
|
Sign up to set email alerts
|

Support for association of HSPG2 with tardive dyskinesia in Caucasian populations

Abstract: Tardive dyskinesia (TD) is a severe adverse effect of chronic antipsychotic drug treatment. In addition to clinical risk factors, TD susceptibility is influenced by genetic predisposition. Recently, Syu et al. (2010) reported a genome-wide association screening of TD in Japanese schizophrenia patients. The best result was association of single-nucleotide polymorphism (SNP) rs2445142 in the HSPG2 (heparan sulfate proteoglycan 2) gene with TD. In the present study, we report a replication study of the five top J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 58 publications
0
24
0
Order By: Relevance
“…BDNF is a neuronal growth and survival peptide that modulates a variety of processes including regulation of the dopamine D3 receptor (DRD3) and could thus be involved in TD through this mechanism (75). The heparan sulfate proteoglycan 2 (HSPG2) gene emerged as the top hit in a GWAS of TD screening by Syu et al (115) and was later replicated in a prospective sample by Greenbaum et al (116) but not in a study by Bakker et al (113).…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…BDNF is a neuronal growth and survival peptide that modulates a variety of processes including regulation of the dopamine D3 receptor (DRD3) and could thus be involved in TD through this mechanism (75). The heparan sulfate proteoglycan 2 (HSPG2) gene emerged as the top hit in a GWAS of TD screening by Syu et al (115) and was later replicated in a prospective sample by Greenbaum et al (116) but not in a study by Bakker et al (113).…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…Research has also implicated variants of the SLC18A2 gene and an interaction between SLC18A2 and DRD2 in TD susceptibility [129,140]. Finally, HSPG2 and DPP6 have emerged as promising candidates for the prediction of TD susceptibility [145,146,149]. …”
Section: Discussionmentioning
confidence: 99%
“…Functional studies of the rs2445142 variant provided further evidence that HSPG2 is involved in TD [145]. Moreover, this association was later replicated by Greenbaum et al [146] in two independent samples, one of Jewish-Israeli ancestry and the other of American-European ancestry. After limiting the control group of the Jewish-Israeli sample to subjects representing an ‘extreme' TD-resistant phenotype, a nominally significant association between the risk rs2445142 G allele and TD was detected.…”
Section: Eps and Tdmentioning
confidence: 93%
“…Moreover, a number of investigations found the relationship between functional gene polymorphisms and antipsychotic-induced TD risk. These genes include the DRD2, DRD3, 5-HT 2A receptor, CYP450, GRIN2A, GSTM1, HSPG2, BDNF and SOD2 [6,[9][10][11]34,35]. However, the antipsychotic-induced adverse reaction (such as TD) in most cases probably does not depend on one single factor or on one single gene variant, but rather on many gene variants, gene-gene or gene-environment interactions [28].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have indicated some risk factors contributed to TD susceptibility, such as age, female gender, dosage and duration of antipsychotics [5]. Recent candidate gene association studies including genome wide association study (GWAS) have identified suscep-tibility genes for TD, such as dopamine D2 (DRD2), DRD3, 5-HT 2A receptor, GLI2, pyrophosphatase 2 (PPA2), heparan sulfate proteoglycan 2 (HSPG2), dipeptidyl peptidase-like protein (DPP)-6 and brainderived neurotrophic factor (BDNF) [6][7][8][9][10][11]. Additionally, several studies have suggested that the gene-gene interactions contributed to individual variations in TD.…”
Section: Introductionmentioning
confidence: 99%